Indications of Platelet-Rich Plasma (PRP) in Dermatology - Berner, Aleksandra; Stencel, Katarzyna; Pękała, Maciej; Olszewska, Anna; Stelmaszak, Karina; Polak, Paulina; Polaszek, Monika; Bogowska, Marta; Matyja, Karolina; Marczyk, Klaudia (Journal of Education, Health and Sport, 2023)
Introduction: PRP is an autologous serum containing high concentrations of platelets and growth factors. It is used in dermatology for a variety of purposes, including hair growth, skin renewal, the removal of acne scars, dermal augmentation, and the treatment of striae distensae. The origins of PRP trace back to the 1970s, originating within the field of hematology as a treatment for patients grappling with thrombocytopenia. The subsequent decades, specifically the 1980s and 1990s, witnessed the integration of PRP into surgical procedures, notably in maxillofacial and plastic surgeries. The rationale underlying the employment and therapeutic potential of a concentrated platelet solution hinges upon their remarkable ability to furnish elevated levels of vital growth factors, thus instigating a regenerative impetus that facilitates repair in tissues characterized by limited innate healing capabilities. This comprehensive review delves into the multifaceted facets of PRP, encompassing mechanisms of action, prevailing indications, existing clinical substantiation, safety considerations, and the burgeoning spectrum of potential applications within the domain of skin condition treatments. Aim of the study: To review the current literature on the use of PRP in the field of dermatology Materials and Methods: We reviewed the literature available in PubMed, using the key words “platelet rich plasma”, “prp”, “autologous platelet rich plasma”, “alopecia”, “anti-aging” Results: PRP has a lot of potential in dermatology and its therapeutic uses are growing. Future research should standardize PRP therapy procedures for particular reasons. Summary: The versatile action of PRP has made it the subject of intense research. However, the reports in the literature to date on its use require further studies on larger groups of people to confirm its effects.